The Impact of Medical Students’ Metacognitive Awareness Level on Their Academic Performance - Shah, Dev K.; Modna, Yuliya (International Journal of Research in Medical Sciences, 2022)
Background: Metacognition influences the academic performance of medical students. The objective of our study was to determine the metacognitive awareness level of medical students in different academic groups in physiology course and develop a guideline on that basis to provide academic support. Methods: A 52-items metacognitive awareness inventory (MAI) devised by Schraw and Dennison was used to assess the metacognition level of low (<70%), average (70-84%), and high performing (>85%) students in a physiology course at Trinity Medical Sciences University (TMSU). Results: Sixty-four students participated in the study. A significant positive correlation (rs=0.462) was found between the total MAI score and the final score in the physiology course. High performing students reported significantly higher score on declarative knowledge (p=0.001); procedural knowledge (p=0.048); implementation of strategies (p=0.003); correction (p=0.000) and evaluation of effectiveness (p=0.000) subscale than their low performing counterparts. Compared to average performing students, high performers were found significantly superior in terms of declarative knowledge (p=0.006), better planning (p=0.047), monitoring (p=0.008) and evaluation of effectiveness (0.004) of the learning process. Conclusions: Metacognitive awareness level has a significant impact on the academic performance of medical students in the physiology course. Low performers need to improve both declarative and procedural knowledge while average performers should augment their declarative knowledge. In terms of regulation of cognition, low performers should develop better implementation, correction, and evaluation skills while average performers should make better planning other than improving their monitoring and evaluating skills.